'Truth'-without-justice-and-reconciliation: a study of the passivity of the Nigerian Government to the confession of the 'Abacha boys' to state terrorism. - Albert, Isaac Olawale (My University, 1943)
Human tights abuses are a problem.The need to discourage this ugly phenomenon and promote reconciliation between the perpetrators and victims of human tights abuses has culminated in the establishment of Truth and Reconciliation Commissions in some parts of the world. The most important of such commissions to be established in Africa was the Truth and Reconciliation Commission which was established in South Africa by Act No. 34 of 1995. Since June 1998, some Nigerians have been asking that their country should join the league of nations that have dealt with their past human rights problems using the path of TRC. The call is made necessary by the abuses that took place in Nigeria between 1993 and 1998. This was the period when General Sani Abacha gave a "bad name" to all the national questions besetting Nigeria since the 1960s: ethnic chauvinism, purposeless leadership, electoral fraud, lack of integrity, corruption, mediocrity, violation of human rights etc.
Paper presented at the University of Witwaterstrand History Workshop on "The TRC: Commissioning the Past", Johannesburg, 1l-14June 1999.
Keywords: Reconciliation, Nigeria; Truth and Reconciliation Commission; Human rights abuses; Abacha, Sani, 1943-1988